The Mediating Role Of Mental Well-Being In The Relationship Between Psychopathy And Online Aggression Among Female Students - Demeter , Dana Rad , Breaz Alina , Toderici Ovidiu , Costin Alina , Delcea Cristian , Roxana Chiș , Sabin Chiș , Gavril Rad; Gavrilă-Ardelean Mihaela (Migration Letters, 2024)
In a rapidly evolving society, the ubiquity of digital technology has reached unprecedented levels, particularly among young individuals who spend a significant portion of their time immersed in the digital realm. However, these interactions can sometimes lead to negative outcomes. Therefore, the present study aims to explore the impact of mental well-being on the relationship between psychopathy and online aggression among non-clinical female students from western Romania. The study sample consisted of 119 female students from Aurel Vlaicu University of Arad, Romania, with a mean age of 27.96 years and a standard deviation of 10.36. Psychopathy (P) was assessed using the Short Dark Triad (SD-3), while Online Aggression (OA) was measured using a single-item scale developed by the authors. Mental Well-Being (MWB) was evaluated using The Warwick-Edinburgh Mental Well-being Scale. The results of the investigation revealed significant correlations among all the variables under study, i.e. between OA and P (r = .24**), MWB and OA (r = -.42**) and P and MWB (r = -.29**). The incorporation of MWB as a mediator in the analysis resulted in the complete mediation of the relationship between P and OA by mental MWB, with a standardized indirect effect of .11 with a 95% coefficient interval spanning from .03 to .23. These results emphasize the crucial role of mental well-being in attenuating aggressive behaviors in the online environment in the case of non-clinical female students.